The Impact of Tertiary Students' Entry Characteristics and their Academic Performance - Afua Nkrumah, Maame (International Journal of African Higher Education, 2021)
This article examines the effect of tertiary students’ entry characteristics on academic performance using the ‘value added’ approach and MET Polytechnic, Ghana as a case study. The input-process–output-context framework presented in the Global Monitoring Report (2005) by Scheerens was used to select appropriate variables for the study. The study focused on three generic courses - African Studies, Communicative Skills, and Computer Literacy. Data from different sources, including secondary data and administrative records from the Polytechnic were analysed using multilevel analysis. The overall effect of the selected variables was mixed and outcomes specific. For example, English language impacted positively on African Studies but negatively on second-semester Computer Literacy, while age and gender had a negative effect on first-semester Computer Literacy. Although the findings may not directly benefit analogous institutions, several lessons, including the need to create appropriate institutional datasets for future comparisons across institutions can be learnt. Key words: Age, gender, department context, previous achievement, SES, ‘value added’.